Oppositional Defiant Disorder and Learning Behavior in Elementary School Students - Wahyuni, Endah Sri; Mahanani, Fatma Kusuma (UK Institute, 2022)
Education is one of the fields that support the national development process. Therefore, education in Indonesia must be further improved so that success in education can also be achieved. One way is to improve or overcome basic problems in the field of education, namely problems related to students, teachers and programs in schools. One of them is about learning behavior and also the opposing behavior of elementary school students. This objective of the study was to determine 1) the description of learning behavior in elementary school students, 2) the description of defiant behavior disorder in elementary school children, 3) the correlation between disruptive behavior disorder and learning behavior in elementary school students. The type of research used by the researcher is quantitative research with a correlational design. The population in this study were elementary school students in the city of Semarang. The characteristics determined by the researchers in taking the population in this study were: a) Elementary School Students in Gunung Pati District and b) Students at SDN Mangunsari 01 dan SDN Plalangan 03. The sampling technique in this study used a purposive sampling technique, namely the technique of determining the sample with consideration certain. The sample in this study amounted to 57 students. The data collection method in this study used various techniques, namely the provision of a questionnaire on learning behavior variables and a questionnaire for opposing behavioral disorders. The result of this research is the value of the correlation coefficient obtained from calculations with the Spearman Rank Correlation with the help of data processing shows the result of 0.620. That is the level of strength of the correlation or correlation between the variables of the tendency of opposing behavior disorders and learning behavior is 0.620. While the significance value or Sig. (2-tailed) owned by both variables is 0.000 where Sig. (2-tailed) 0.000 less than 0.05 or 0.01. These results indicate that the research hypothesis is accepted.Pendidikan merupakan salah satu bidang yang menjadi pendukung dalam proses pembangunan nasional. Oleh karena itu, pendidikan di Indonesia harus lebih ditingkatkan agar keberhasilan dalam pendidikan juga dapat tercapai. Salah satu caranya adalah dengan memperbaiki atau mengatasi masalah-masalah mendasar dalam bidang pendidikan, yaitu masalah yang berkaitan dengan siswa, guru maupun program yang ada di sekolah. Salah satunya adalah mengenai perilaku belajar dna juga perilaku menentang yang dimiliki oleh siswa Sekolah Dasar. Penelitian ini bertujuan untuk mengetahui 1) Gambaran perilaku belajar pada siswa Sekolah Dasar, 2) Gambaran gangguan perilaku menentang pada anak Sekolah Dasar, 3) Hubungan antara gangguan perilaku menentang dengan perilaku belajar pada siswa Sekolah Dasar. Jenis penelitian yang digunakan oleh peneliti adalah penelitian kuantitatif dengan desain korelasional. Populasi dalam penelitian ini adalah siswa Sekolah Dasar yang ada di Kota Semarang. Karakteristik yang ditetapkan oleh peneliti dalam pengambilan populasi pada penelitian ini adalah: a) Siswa Sekolah Dasar di Kecamatan Gunungpati dan b) Siswa di SDN Mangunsari 01 dan SDN Plalangan 03. Teknik sampling dalam penelitian ini menggunakan teknik purposive sampling, yaitu teknik penentuan sampel dengan pertimbangan tertentu. Sampel dalam penelitian ini berjumlah 57 siswa. Metode pengumpulan data dalam penelitian ini menggunakan berbagai teknik yaitu pemberian kuesioner variabel perilaku belajar dan kuesioner variabel gangguan perilaku menentang. Hasil dari penelitian ini adalah nilai dari koefisien korelasi yang diperoleh dari perhitungan dengan Korelasi Spearman Rank dengan bantuan pengolah data menunjukkan hasil sebesar 0,620. Artinya, tingkat kekuatan hubungan atau korelasi antara variabel kecenderungan gangguan perilaku menentang dengan perilaku belajar adalah sebesar 0,620. Sedangkan nilai signifikansi atau Sig. (2-tailed) yang dimiliki oleh kedua variabel adalah sebesar 0,000 dimana Sig. (2-tailed) 0,000 kurang dari 0,05 atau 0,01. Hasil tersebut menunjukkan bahwa hipotesis penelitian ini diterima.